Analysis of Lesson Plan, Learning Process, Teacher Competence Based on The Indonesian Economics - hairunisya, nanis (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
This research aims to analyze the lesson plan, learning process, and teacher competence based on the Indonesian economics, to develop the subject of economic learning. The object of this research is located in 6 (six) cities/regencies in East Java namely Bondowoso, Pamekasan and Trenggalek, Madiun, Blitar and Kediri in 2016. The research method used is qualitative method. The results showed that none of the lesson plan component belonged to the category of excellent quality. Lesson plan is more functioned as the fulfillment of administrative requirements, rather than as a guide in the implementation of learning. The learning process is implemented good, the assessment of learning process is basically closely related to the results of the assessment of the competence of teachers conducted on input evaluation. The quality of learning is influenced by the condition of students, schools that have students with high passion and high motivation to learn, the implementation of learning will be conducive. Another thing is the lack of material presented by the teacher on the core activities of learning. The teacher often reveals a less precise conceptabout economic theory, as well as the disclosure of events or economic numerical data, teachers are less trying to extract material from economic books to enrich learning materials.